Effects of Diuron [3-(3,4-dichlorophenyl)-1,1-dimethylurea] on the urinary bladder of male Wistar rats - Nascimento, Merielen Garcia; Oliveira, Maria Luiza Cotrim Sartor de [UNESP]; Lima, Adriano Silva; Camargo, João Lauro Viana de [UNESP] (Elsevier B.V., 2006)
Diuron (3-(3,4-dichlorophenyl)-1,1-dimethylurea) is a substituted urea herbicide widely used on agricultural crops such as soy, cotton and sugar cane. In a previous long-term study this herbicide exerted carcinogenic activity on the urinary bladder mucosa of male Wistar rats. In general, the genotoxic and mutagenic potentials of Diuron are considered to be negative. The present study aimed to evaluate the mode of action of Diuron on the urinary bladder mucosa of male Wistar rats. Six-week old male Wistar rats were fed pelleted Nuvilab diet mixed with Diuron at 125, 500 and 2500 ppm. As a positive control, 8.3% sodium saccharin (NaS) was fed in the diet. Preceding the sacrifice of the animals at the 20th week, urinary pH was measured and the genotoxic potential of Diuron was evaluated by the comet assay. Histological urothelial lesions in the urinary bladder and in the renal pelvis mucosa, cell proliferation/apoptosis evaluations, and scanning electron microscopy (SEM) of the urinary bladder mucosa were also performed. No DNA changes were found in urothelial or peripheral blood cells, and urinary pH was comparable to controls in all Diuron groups. In the urinary bladder urothelium, the incidence of simple hyperplasia (SH) by light microscopy was significantly increased (7/10; p < 0.005) in the 2500 ppm Diuron group but not at the lower doses. By SEM, three of five animals treated with 2500 ppm Diuron showed urothelial cell necrosis and hyperplasia. In the renal pelvis, the incidence of SH was significantly increased in the Diuron 500 and 2500 ppm and in the NaS 8.3% groups. Cell proliferation was significantly increased in the Diuron 2500 ppm, (p < 0.05) and NaS 8.3% (p < 0.05) groups. The results indicate that a high dietary concentration of Diuron is associated with urothelial necrosis and continuous regenerative cell proliferation that leads to urothelial hyperplasia. (c) 2006 Elsevier B.V.. All rights reserved.
Keywords: Diuron; [3-(3,4-dichlorophenyl)-1,1-dimethylurea]; rat urinary bladder; urothelial hyperplasia; carcinogenesis; cytotoxicity; cell proliferation